γ-Secretase as a Therapeutic Target for Treatment of Alzheimer's Disease - Tomita, Taisuke; Iwatsubo, Takeshi (Current Pharmaceutical Design, 2006)
Alzheimer's disease (AD) is the most common cause of dementia with aging, that is pathologically characterized by senile plaques that contain amyloid-b peptides (Aβ) and neurofibrillary tangles comprised of phosphorylated tau. Genetic and biological studies provide evidence that the production and deposition of Aβ contribute to the etiology of AD. g-Secretase is the pivotal enzyme in generating the C terminus of Aβ, that determines its aggregability and propensity for deposition. Drugs that regulate the production of Aβ by inhibiting g-secretase activity could provide an effective therapeutics for AD, although recent studies suggest that g-secretase plays important roles in novel signaling pathways that play essential roles in embryonic development. This review focuses on recent progresses in the g-secretase biology that shed substantial light on the proteolytic mechanism, regulation and composition of this unusual enzyme. Moreover, we review the recent development of inhibitors and provide a direction for the effective treatment of AD through inhibition of g-secretase activity.
Keywords: intramembrane proteolysis